Pengaruh Good Corporate Governance terhadap Profitabilitas dengan Kualitas Audit sebagai Variabel Moderasi - Wijayanti, Ajeng; Gea, Odorikus Otarman; Mawarni, Riska (Jurnal Manajemen Bisnis dan Keuangan, 2023)
This study aims to examine the effect of good corporate governance (managerial ownership, institutional ownership, and independent board of commissioners) on profitability with audit quality as a moderating variable. The population of this study is a manufacturing company listed on the Indonesia Stock Exchange. The sample selection method is the purposive sampling method. The number of samples used in this study was 22 companies, and the number of years of research was five years (2016-2020) so the total observation data used was 110. The data analysis method used was Structural Equation Modeling-Partial Least Square (SEM-PLS). using smartPLS software version 3. The results of this study show that institutional ownership and independent board of commissioners significantly influence the profitability variable, while the effect of managerial ownership on profitability is not significant, the effect of audit quality on profitability is also not significant, audit quality is not able to moderate the effect of variables managerial ownership, institutional ownership, and independent board of commissioners on Profitability. The implication of this research is to provide strategic recommendations for companies in increasing profitability.